Chemical Ocular Burns 2010
DOI: 10.1007/978-3-642-14550-6_5
|View full text |Cite
|
Sign up to set email alerts
|

Physiopathology of the Cornea and Physiopathology of Eye Burns

Abstract: The barriers of the eye differ from that of skin in dimensions and mucosal organization: there are epithelial cellular barriers made of lipid layers on the eye and dry surfaces made of proteins in the stratified surfaces of the skin. Skin is protected by a superficial outer fatty film, the stratum corneum, and covered by a thick layer of cells, the basal cellular layer. Thanks to these thick layers, skin has a high resistance to initial diffusion of aqueous fluids and less resistance to lipophilic solvents and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…The concentrations of glucose and protein are about 10 and 30 times lower, respectively, in tear fluid than in serum [45]. The chemical tests run by us on the fresh amniotic membrane specimens revealed a slightly higher Na + , K+ and Cl -, ion concentration (Na + =152 mEq/L; K + =5.74 mEq/ L; Cl -=131.6 mEq/L) than in serum [32], yet comparable to that of ions in the aqueous humor (Na + =152 mEq/L; K + =3.9 mEq/L; Cl -=131.6mEq/L), as reported by Schrage [46].…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The concentrations of glucose and protein are about 10 and 30 times lower, respectively, in tear fluid than in serum [45]. The chemical tests run by us on the fresh amniotic membrane specimens revealed a slightly higher Na + , K+ and Cl -, ion concentration (Na + =152 mEq/L; K + =5.74 mEq/ L; Cl -=131.6 mEq/L) than in serum [32], yet comparable to that of ions in the aqueous humor (Na + =152 mEq/L; K + =3.9 mEq/L; Cl -=131.6mEq/L), as reported by Schrage [46].…”
Section: Resultssupporting
confidence: 70%
“…We found a total antioxidant capacity (TAC) in hAM of 1.1±0.1 mmol/L (tables 1 and 2), lower than that in serum [46]. However, a team of authors from India reported that tears from healthy people have a total antioxidant capacity (TAC) of 0.7 ± 0.18 mmol/L, with a range of 0.41-1.03mmol/L [42], i.e.…”
Section: Resultsmentioning
confidence: 83%